The risk of upper gastrointestinal bleeding associated with concomitant proton pump inhibitor administration during dual antiplatelet therapy with aspirin and prasugrel: a retrospective single-center study - Yutaro Ide; Go Morikawa; Kyohei Yoshida; Yuki Takano; Ken Kubota; Katsuko Okazawa; Takeo Yasu (BMC, 2024)
Abstract Objective Dual‐antiplatelet therapy (DAPT) and proton pump inhibitor (PPI) are frequently prescribed after percutaneous coronary intervention (PCI) with drug-eluting stents (DES) placement. However, studies that evaluate the optimal PPI when used as primary prevention in patients without a history of peptic ulcer disease or upper gastrointestinal bleeding (UGIB), particularly in the context of DAPT involving prasugrel, are lacking. This study aimed to assess the efficacy and safety of PPI use in preventing UGIB in this patient population. Methods This study included patients who underwent PCI with coronary stent placement for acute coronary syndrome or stable angina at our institution from January 2015 to December 2020. Eligible patients started DAPT with aspirin and prasugrel and concomitantly received PPI therapy (lansoprazole or esomeprazole), with a follow-up period of two years. The primary endpoint was UGIB incidence, diagnosed during follow-up, serving as an efficacy measure. Secondary endpoints included the assessment of major bleeding (as defined by the Thrombolysis in Myocardial Infarction major bleeding criteria) and clinically relevant non-major bleeding events. Safety outcomes focused on adverse event incidence attributable to PPI use. Results Among the 165 patients analyzed, 109 and 56 were included in the lansoprazole and esomeprazole groups, respectively, with cumulative incidence of UGIB at 96 weeks of 0.9% (1/109) and 3.6% (2/56). No significant differences in terms of major bleeding events or other bleeding outcomes were observed between the two groups. Adverse events related to PPI use were reported as diarrhea/soft stools in 7 (6%) cases and thrombocytopenia in 1 (1%) case in the lansoprazole group, whereas no such events were observed in the esomeprazole group. No clinically significant hematologic or biochemical abnormalities were reported. Conclusion This study evaluated the efficacy and safety of PPIs in combination with DAPT, including prasugrel, following PCI, and suggests that lansoprazole and esomeprazole may offer comparable efficacy in preventing UGIB.